Bilingual Education vs English-only Approach at Australia’s Northern Territory Schools - Rahman, Fadhlur (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
The present library research highlights the “English-only” approach used in the Aboriginal classrooms in Northern Territory (NT) schools, Australia. This library study collects its data from five decades (1968-2018) of research and theorisation on the implementation of English instruction at Indigenous classrooms in Australia by referring to the changes of approaches from bilingual instruction policy to the current “English-only” approach. The writer then reports the problems occurred in the implementation of this approach in the specific classroom interaction. Factors like socio-cultural gap and dysfunctional discourse were found to be influencing the ineffective English-only classroom in the NT schools. What alternatives may have been tried in the Northern territory schools and to what degree of success?